Pesan Komunikasi Islam dalam Hata Situtur Poda Adat Pernikahan Suku Mandailing Desa Hapung Kabupaten Padang Lawas - Hasibuan, Muhammad Darisal (YASIN, 2023)
This research aims to determine the content of Islamic communication messages in hata situtur poda, and the media used by the bride and groom. This type of research is qualitative research with a phenomenological approach. The data sources in this research are primary and secondary data sources. Primary data sources are video files, traditional leaders who understand the tradition of giving hata situtur poda and secondary data sources obtained from books, magazines, articles related to the direction of this research. The data collection tools used were interviews, observation and documentation. Data analysis techniques using data classification steps, checking data completeness, data description and drawing conclusions. Based on the research results, it was found that the contents of Islamic communication messages in hata situtur poda messages include praise to Allah, advice from parents to children, advice from relatives to the bride and groom, commendable morals, mutual respect, love for family, developing an attitude of helping each other. , and mutual advice, a sense of responsibility, happiness in life in this world and the hereafter and prayers for safety. The media used are traditional and modern media. Traditional media are traditional mats, and media when suyup-suyup. Namely a plate/talam containing chicken cooked in large pieces, boiled free-range chicken eggs, salt and rice. Meanwhile, modern media is a microphone that is used as a loudspeaker to provide advice to the bride and groom.